Clinical and imaging clues to the diagnosis and follow‐up of ptosis and ophthalmoparesis. Issue 6 (29th September 2022) - Keene, Kevin R.; Kan, Hermien E.; van der Meeren, Stijn; Verbist, Berit M.; Tannemaat, Martijn R.; Beenakker, Jan‐Willem M.; Verschuuren, Jan J.G.M.
Abstract: Ophthalmoparesis and ptosis can be caused by a wide range of rare or more prevalent diseases, several of which can be successfully treated. In this review, we provide clues to aid in the diagnosis of these diseases, based on the clinical symptoms, the involvement pattern and imaging features of extra‐ocular muscles (EOM). Dysfunction of EOM including the levator palpebrae can be due to muscle weakness, anatomical restrictions or pathology affecting the innervation. A comprehensive literature review was performed to find clinical and imaging clues for the diagnosis and follow‐up of ptosis and ophthalmoparesis. We used five patterns as a framework for differential diagnostic reasoning and for pattern recognition in symptomatology, EOM involvement and imaging results of individual patients. The five patterns were characterized by the presence of combination of ptosis, ophthalmoparesis, diplopia, pain, proptosis, nystagmus, extra‐orbital symptoms, symmetry or fluctuations in symptoms. Each pattern was linked to anatomical locations and either hereditary or acquired diseases. Hereditary muscle diseases often lead to ophthalmoparesis without diplopia as a predominant feature, while in acquired eye muscle diseases ophthalmoparesis is often asymmetrical and can be accompanied by proptosis and pain. Fluctuation is a hallmark of an acquired synaptic disease like myasthenia gravis. Nystagmus is indicative of a central nervous system lesion. Second, specific EOM involvement patterns can also provide valuable diagnostic clues. In hereditary muscle diseases like chronic progressive external ophthalmoplegia (CPEO) and oculo‐pharyngeal muscular dystrophy (OPMD) the superior rectus is often involved. In neuropathic disease, the pattern of involvement of the EOM can be linked to specific cranial nerves. In myasthenia gravis this pattern is variable within patients over time. Lastly, orbital imaging can aid in the diagnosis. Fat replacement of the EOM is commonly observed in hereditary myopathic diseases, such as CPEO. In contrast, inflammation and volume increases are often observed in acquired muscle diseases such as Graves' orbitopathy. In diseases with ophthalmoparesis and ptosis specific patterns of clinical symptoms, the EOM involvement pattern and orbital imaging provide valuable information for diagnosis and could prove valuable in the follow‐up of disease progression and the understanding of disease pathophysiology.